Optical and Structural Investigation of CdSe Quantum Dots Dispersed in PVA Matrix and Photovoltaic Applications. (23rd October 2013) - Phukan, Pallabi; Saikia, Dulen
Abstract : CdSe quantum dots (QDs) dispersed in polyvinyl alcohol (PVA) matrix with their sizes within the quantum dot regime have been synthesized via a simple heat induced thermolysis technique. The effect of the concentrations of the cadmium source on the optical properties of CdSe/PVA thin films was investigated through UV-Vis absorption spectroscopy. The structural analysis and particle size determination as well as morphological studies of the CdSe/PVA nanocomposite thin films were done with the help of X-ray diffraction (XRD) and transmission electron microscopy (TEM). The XRD analysis reveals that CdSe/PVA nanocomposite thin film has a hexagonal (wurtzite) structure. A prototype thin film solar cell of CdSe/CdTe has been synthesized and its photovoltaic parameters were measured.